COMPLEXES OF SILVER, LEAD, CALCIUM WITH BISPHOSPHONIC LIGANDS - A. V. Galantsev; M. Haukka; D. V. Drobot (Тонкие химические технологии, 2018)
It is interesting in chemical terms and promising in the applied production of new complexes of metals with bisphosphonic ligands with a popular set of consumer properties. To date, little has been studied chemistry of bisphosphonic acid complexes with the basic structure of 1-hydroxymethylene-bisphosphonic acid with a side chain containing 11 carbon atoms and ending with an amino group. The main objective is to obtain new bisphosphonates of s-, p -, d - and f-elements, their characterization by a complex of physical and chemical research methods (NMR and IR spectrometry, RSA, DTA, optical microscopy, laser diffraction) and to identify new applications of bisphosphonic acids and their salts. In the course of the work, complexes of Ag, Pb, Ca, with 1-hydroxymethylene-bisphosphonic acid (H2N(CH2)xC(OH)(H2PO3)2) and its derivatives, the side chain ends with an amino group, its length is 11 carbon atoms. Crystal structures of metal-bisphosphonate complexes with the general formula H2N(CH2)10C(OH)(HPO3)xM (M = Ag, Pb, Ca) were determined. The complexes were characterized by IR spectroscopy and 31P solid-state NMR spectroscopy, RSA. The areas of practical use of the complexes are outlined. It is shown, by the example of wastewater in Kuopio, Finland, that bisphosphonic acids can be used for wastewater treatment of enterprises from heavy metals (M =Pb, Zn, Cd, etc.).